Penggunaan User Experience Questionnaire Pada Aplikasi ISX Di PT Indotirta Sriwijaya Perkasa - Risma Anggraini; Desi Pibriana; Anugerah Widi (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
PT Indotirta Sriwijaya Perkasa is a company in the production and trade of bottled Demineral Water which uses the ISX application to help manage sales invoices, taxes, travel letters, notes, and reports. based on the results of interviews with users, the ISX application still has shortcomings and obstacles, namely there are features that have no function but are on the display so that it looks a lot of features that must be filled in by the user, and users mention when using the application the eyes become bored because the application is not full of various colors. To overcome these problems, an analysis will be carried out measuring the user experience of the ISX application using the User Experience Questionnaire (UEQ) method which can produce recommendations to improve the quality of the ISX application user experience. To analyze the data, Data Analysis Tools version 11 is used as a user experience measurement tool. This study uses a saturated sampling technique with a sample of 35 ISX application user respondents. The results obtained are positive evaluation results from the mean and variance, and in the Benchmark data there are 4 Below Average scales, 1 Bad scale, and 1 Above Average scale.